Iowa Birdline update, July 29, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for July 29, 1991. The highlights for the update include sightings of nine shorebird species, an early Ruddy Turnstone and a Summer Tanager. Also included are handwritten notes with sightings of two Yellow-headed Blackbirds and a Carolina Wren. Epson - sheet feed/flatbed